2016
DOI: 10.1016/j.npep.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of receptor binding and functional characteristics of hemopressin(1–7)

Abstract: The orally active, α-hemoglobin derived hemopressin (PVNFKFLSH, Hp(1-9)) and its truncated (PVNFKFL, Hp(1-7) and PVNFKF, Hp(1-6)) and extended ((R)VDPVNFKFLSH, VD-Hp(1-9) and RVD-Hp(1-9)) derivatives have been postulated to be the endogenous peptide ligands of the cannabinoid receptor type 1 (CB1). In an attempt to create a versatile peptidic research tool for the direct study of the CB1 receptor-peptide ligand interactions, Hp(1-7) was radiolabeled and in vitro characterized in rat and CB1 knockout mouse brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Dvorácskó et al . recently reported that a truncated hemopressin peptide (PVNFKFL, Hp(1‐7)), a related family member of pepcan‐12, could act as an allosteric ligand or indirect regulator of the endocannabinoid system rather than an endogenous ligand as postulated previously.…”
Section: Negative Allosteric Modulators (Nams) Of the Cb1 Receptormentioning
confidence: 74%
“…Dvorácskó et al . recently reported that a truncated hemopressin peptide (PVNFKFL, Hp(1‐7)), a related family member of pepcan‐12, could act as an allosteric ligand or indirect regulator of the endocannabinoid system rather than an endogenous ligand as postulated previously.…”
Section: Negative Allosteric Modulators (Nams) Of the Cb1 Receptormentioning
confidence: 74%
“…Others have also failed to find evidence for hemopressin activity at the CB1 receptor. [35][36][37] We therefore turned our attention to the natural plant-derived CBD. CBD has a low affinity for the CB1 receptor and functions as a noncompetitive allosteric antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Hp was originally identified as an inverse agonist/antagonist of CB1 [ 154 ]. A few years ago, a study revealed that Hp slightly activated G proteins and functioned as a very weak agonist, proposing a hypothesis that Hp indirectly interacts with CB1 [ 155 ]. In addition, it is confirmed that Hp does not function as a NAM of CB1 in a study using electrophysiology [ 156 ].…”
Section: Novel Cannabinoids From Animal Sourcesmentioning
confidence: 99%